2020
DOI: 10.1016/j.jcot.2019.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinic-radiological outcome of cross pinning versus lateral pinning for displaced supracondylar fracture of humerus in children: A randomized controlled trial

Abstract: Introduction: Supracondylar fracture of humerus (SFH) is frequently encountered in the immature skeleton, [1] predominantly in the non-dominant extremity. Aim: This study compared the clinic-radiological outcome between cross pinning with lateral pinning for fixation of displaced supracondylar fracture of humerus in children. Materials and methods: All eligible patients were randomized into two groups, group I for lateral pinning and group II for cross pinning. Before passing medial pin in group II a stab inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Larson et al reported that crossed pinning is biomechanically more stable than lateral pin constructs but carries a higher risk of ulnar nerve injury during the insertion of the medial pin [35]. Afaque et al and Pavone et al demonstrated that there is no significant difference between lateral pinning and crossed pinning in terms of functional outcome, biomechanical stability, and incidence of complications [10,36].…”
Section: Iatrogenic Nerve Injuriesmentioning
confidence: 99%
“…Larson et al reported that crossed pinning is biomechanically more stable than lateral pin constructs but carries a higher risk of ulnar nerve injury during the insertion of the medial pin [35]. Afaque et al and Pavone et al demonstrated that there is no significant difference between lateral pinning and crossed pinning in terms of functional outcome, biomechanical stability, and incidence of complications [10,36].…”
Section: Iatrogenic Nerve Injuriesmentioning
confidence: 99%
“…Meanwhile, playing caused the maximum injury (45.2%) in the late group, which is consistent with other studies. [10][11][12][13] The treatment option besides closed reduction is opening reduction with pinning. Open reduction is indicated in the cases of failed closed reduction, loss of pulse or poorly perfused hand following reduction and in the case of open fracture.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent literature show the use of only lateral pinning as sufficient for fixing supracondylar fracture. [11][12][13][14][15] Bayisenga J. et al evaluated the early outcome of open reduction and internal fixation of Lagrange & Rigault stage IV supracondylar humerus fractures in children in Rwanda, using K-wires pinning. The result confirmed the method's effectiveness, especially in cases of delayed treatment and in settings with no intensifier imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the complex vascular and neural structures surrounding the elbow make these structures prone to injury during trauma and surgery. Cubitus varus has been reported to be between 5 and 15% after surgical treatment (6,7), and it has been reported that ulnar nerve injury can be seen in 15% of the patients after medial pinning (8). The surgery recommended to be performed is the fixation of the fracture with the pins after an open or a closed reduction.…”
Section: Introductionmentioning
confidence: 99%